Obtain a polynomial f such that   where i = 2 to n...

Answers ( 4 )

  1. marcel thiele
    marcel thiele
    Let xi = sum(xi)
    Multiply both side by (x-1)
    f(x) = sum(xi+1) -sum(xi),                  and sum(xi+1) = sum(xi) +xn+1 - x2
    f(x) = sum(xi) + xn+1 - x2 -sum(xi)
    f(x) = xn+1 - x2
    I hope it helps.
  2. viktor sauer
    viktor sauer
  3. mustafa kavakl?o?lu
    mustafa kavakl?o?lu
    Look at the simplest case: when i=2 to 3
    sum(xi)*(x-1) = (x2 +x3)(x-1) = x(x2 + x3) -(x2 + x3)(1) = (x2+1 +x3+1) - (x2 + x3)... etc... getit? :)
  4. liam thompson
    liam thompson
    I think i didnt get

    how did you get to

    Multiply both side by(x-1) to the sum ( x ^ i)
    f(x) =sum(xi+1) -sum(xi),                  and sum(xi+1) = sum(xi) +xn+1 - x2


Leave a reply